Excitation energy transfer between monomolecular layers of light harvesting LH2 and LH1-reaction centre complexes printed on a glass substrate. Issue 14 (17th June 2020) - Huang, Xia; Vasilev, Cvetelin; Hunter, C. Neil
Abstract : Remarkably stable artificial light-harvesting arrays capable of harvesting and trapping solar energy were fabricated using purified bacterial pigment–protein complexes. Abstract : Light-harvesting 2 (LH2) and light-harvesting 1 – reaction centre (RCLH1) complexes purified from the photosynthetic bacterium Rhodobacter ( Rba. ) sphaeroides were cross-patterned on glass surfaces for energy transfer studies. Atomic force microscopy (AFM) images of the RCLH1 and LH2 patterns show the deposition of monomolecular layers of complexes on the glass substrate. Spectral imaging and fluorescence life-time imaging microscopy (FLIM) revealed that RCLH1 and LH2 complexes, sealed under physiological conditions, retained their native light-harvesting and energy transfer functions. Measurements of the amplitude and lifetime decay of fluorescence emission from LH2 complexes, the energy transfer donors, and gain of fluorescence emission from acceptor RCLH1 complexes, provide evidence for excitation energy transfer from LH2 to RCLH1. Directional energy transfer on the glass substrate was unequivocally established by using LH2-carotenoid complexes and RCLH1 complexes with genetically removed carotenoids. Specific excitation of carotenoids in donor LH2 complexes elicited fluorescence emission from RCLH1 acceptors. To explore the longevity of this novel nanoprinted photosynthetic unit, RCLH1 and LH2 complexes were cross-patterned on a glass surface and sealed under a protective argon atmosphere. The results show that both complexes retained their individual and collective functions and are capable of directional excitation energy transfer for at least 60 days.